2005
DOI: 10.1001/jama.294.19.2437
|View full text |Cite|
|
Sign up to set email alerts
|

High-Dose Atorvastatin vs Usual-Dose Simvastatin for Secondary Prevention After Myocardial Infarction<SUBTITLE>The IDEAL Study: A Randomized Controlled Trial</SUBTITLE>

Abstract: Context Evidence suggests that more intensive lowering of low-density lipoprotein cholesterol (LDL-C) than is commonly applied clinically will provide further benefit in stable coronary artery disease. Objective To compare the effects of 2 strategies of lipid lowering on the risk of cardiovascular disease among patients with a previous myocardial infarction (MI). Design, Setting, and Participants The IDEAL study, a prospective, randomized, open-label, blinded end-point evaluation trial conducted at 190 ambulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
783
5
55

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,446 publications
(869 citation statements)
references
References 23 publications
(19 reference statements)
26
783
5
55
Order By: Relevance
“…1) so that the several large trials did not confound results from the smaller trials. Six long‐term trials18, 20, 21, 22, 23, 28 (see footnote to Table 1 for trial details) investigating the effect of atorvastatin on CV outcomes were analyzed both individually and pooled according to treatment group; the median study duration was 3.1–4.9 years. The remaining 52 short‐term studies (≤2 years) were pooled according to treatment group; the median study duration was 4–72 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) so that the several large trials did not confound results from the smaller trials. Six long‐term trials18, 20, 21, 22, 23, 28 (see footnote to Table 1 for trial details) investigating the effect of atorvastatin on CV outcomes were analyzed both individually and pooled according to treatment group; the median study duration was 3.1–4.9 years. The remaining 52 short‐term studies (≤2 years) were pooled according to treatment group; the median study duration was 4–72 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Long‐term CV outcomes trials with atorvastatin,17, 18, 19, 20, 21, 22, 23 as well as other statins,24, 25 have demonstrated the safety of this class in a range of populations. However, compared with the wealth of evidence from Western populations, the availability of statin safety data from Asian populations is limited, which may be a contributing factor in the underutilization of statins for the treatment of dyslipidemia in this ethnic group.…”
Section: Introductionmentioning
confidence: 99%
“…Given that CAD patients differ widely in history of and risk factors for vascular disease, there is a potential range in absolute benefit from intensification of LLT. Previously, we derived a prediction model in the Treating to New Targets (TNT) trial population that estimates 5‐year absolute treatment effect of intensive versus standard LLT with statins on recurrent vascular events for an individual patient, which was validated in the Incremental Decrease in End point through Aggressive Lipid‐lowering (IDEAL) trial population 7, 8, 9. With this model, we are able to estimate the individual 5‐year absolute risk reduction (ARR) for vascular events based on simple patient characteristics 7, 10.…”
Section: Introductionmentioning
confidence: 99%
“…The 2013 American College of Cardiology (ACC)/American Heart Association (AHA) Guideline on the Treatment of Blood Cholesterol to Reduce Atherosclerotic Cardiovascular Risk in Adults acknowledges the limitations of existing data on older individuals and recommends individualizing the decision to initiate statins for primary prevention in adults >75 years 1. For secondary prevention, 3 trials found that high‐intensity statin therapy reduced cardiovascular events more than moderate‐intensity statin therapy, but these trials enrolled few patients >75 years and none >80 years8, 9, 10; however, there was sufficient evidence for moderate‐intensity statin therapy in secondary prevention patients of any age 11. The most recent 2016 US Preventive Services Task Force Recommendation Statement on Statin Use for the Primary Prevention of Cardiovascular Disease similarly avoids firm recommendations about statins for older adult patients (>75 years old), as do the European Society of Cardiology/European Atherosclerosis Society guidelines for the management of dyslipidemias in patients >80 years old, with insufficient evidence to make a recommendation in this population 12, 13…”
mentioning
confidence: 99%